Towards a necessary regenerative urban planning: Insights from community-led initiatives for ecocity transformation - Crowley, Duncan (2021)
This article suggests that to adequately tackle climate breakdown, urban planning needs to move beyond sustainability to incorporate regenerative development frameworks. Key to this is activating and increasing citizen participation in a fractal-like, multi scaled, community-led, bottom up planning process, where active citizens design, construct and are part of the futures they desire for their territories. 2019’s declarations of climate emergency show that decades of sustainable development have not worked. The Sustainable Development Goals are a positive step, but sustainability’s dependence on economic growth is problematic. Recognising Earth’s limits, this article builds on degrowth ideas and doughnut economic frameworks to examine the role of community-led urban transitions in catalysing a regenerative world, where ecocities are the normative goal of contemporary cities. Challenges in scaling the Global Ecovillage Network’s process to large cities are identified and some radical governance experiments examined. Attempting to bridge activism and academia, a transdisciplinary participative action research method is used to develop a Communities of Practice ecosystem to support an eco-social just transition. This work contributes to the European Network for Community-Led Initiatives on Climate Change and Sustainability, ECOLISE, the Horizon 2020 project UrbanA investigating Sustainable and Just Cities, and the Communities for Future action platform enabling translocal communities to connect, co-create a knowledge commons and help shape policy. Insights from Lisbon are examined with three community-led initiatives; Bela Flor, Ajuda and Marvila. These processes are still at the margins, but could soon become core activities of regenerative urban planning. Re-Making our cities is everyone’s business.